2001
DOI: 10.1089/104303401750476294
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Hyaline Cartilage by Cell-Mediated Gene Therapy Using Transforming Growth Factorβ1-Producing Fibroblasts

Abstract: Transforming growth factor beta (TGF-beta) has been considered as a candidate for gene therapy of orthopedic diseases. The possible application of cell-mediated TGF-beta gene therapy as a new treatment regimen for degenerative arthritis was investigated. In this study, fibroblasts expressing active TGF-beta 1 were injected into the knee joints of rabbits with artificially made cartilage defects to evaluate the feasibility of this therapy for orthopedic diseases. Two to 3 weeks after the injection there was evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 21 publications
(25 reference statements)
0
49
0
2
Order By: Relevance
“…27,28 TGF-b1 has been used as a key inductor of chondrogenesis in many in vivo and in vitro studies, as it stimulates cell proliferation and synthesis of major components of ECM, GAG and collagen. [29][30][31] It was chosen for use in this study because it is one of the best characterized and most potent chondrogenic growth factors. The results of this study showed that all groups that underwent transplantation of BMCs have a high content of GAGs, but only the repair tissue from defects treated with TGF-b1 gene plugs had a very high content of collagen type II similar to native cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 TGF-b1 has been used as a key inductor of chondrogenesis in many in vivo and in vitro studies, as it stimulates cell proliferation and synthesis of major components of ECM, GAG and collagen. [29][30][31] It was chosen for use in this study because it is one of the best characterized and most potent chondrogenic growth factors. The results of this study showed that all groups that underwent transplantation of BMCs have a high content of GAGs, but only the repair tissue from defects treated with TGF-b1 gene plugs had a very high content of collagen type II similar to native cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have the capacity to stimulate undesirable activities in cells of nontarget, collateral tissues. Although there is a report of repair of cartilage lesions in rabbits following ex vivo gene transfer of TGF-b1 to synovium using genetically modified fibroblasts, 36 the consensus among several other studies is that such a procedure can be quite toxic, resulting in severe joint fibrosis, extreme swelling, osteophytes and cartilage degeneration. 37,38 Similarly, overexpression of BMP-2 in the synovial lining of knees of mice from either direct or ex vivo gene transfer caused the formation of ectopic cartilage throughout the joint capsule and growth of large osteophytes.…”
Section: Gene Transfer To Cells In the Synovial Liningmentioning
confidence: 99%
“…[74][75][76] Genes encoding other growth factors known to promote cartilage differentiation of chondrocyte progenitors have also been studied. For example, Lee et al 77 have utilized fibroblasts engineered to express transforming growth factor-b 1 (TGF-b 1 ) in rabbit knee joints with experimental cartilage defects. In this model, fibroblasts served as vehicles for the delivery of TGF-b 1 to host chondrocytes and chondrocyte progenitors.…”
Section: Stem-cell-based Gene Therapy Applications For Cartilagementioning
confidence: 99%